DESAIN PEMBELAJARAN DARING BERBASIS VIDEO ANIMASI - Rahmatullah Rahmatullah; Inanna Inanna; Mustari Mustari (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
This study aims to develop an online learning design based on animated videos in economics. This study uses a research and development approach with the stages of initial analysis, material identification, product preparation, and testing. After the product is developed, a feasibility evaluation is carried out by experts to see the feasibility and the suitability between the content, the completeness of the design, and its attractiveness. In carrying out the design process, teachers can take advantage of available technology software, for example Explee. Analysis of the data used to interpret the results of this study, namely content analysis and student responses/tests. This analysis is used to process all information or research data obtained from the beginning to the end of the research implementation, in the form of input, feedback, criticism and suggestions for improvement according to predetermined indicators. The categories used in interpreting the results of the analysis are very good, good, good enough, not good and very bad. The results of the study show that the attractively designed animated videos are used by teachers, so that the online learning process runs effectively.Keywords: Learning Design; Animated Videos; Explee App